KONTROVERSI TAFSIR SAINS (Studi Komparatif Tentang Pemikiran Thanthawi Jauhari dan Mahmud Syaltut dalam Penafsiran Surah Al-Dukhan Ayat 10-11) - Hurin Aini (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the controversy of scientific exegesis through a comparative study of Thanthawi Jauhari and Mahmud Syaltut in interpreting Surah Al-Dukhan verses 10–11, particularly the meaning of dukhan. This issue reflects the tension between contextualizing the Qur'an with modern science and maintaining methodological validity in interpretation. This research employs a qualitative approach using library research design and comparative analysis. Data were collected through documentation of primary tafsir works and relevant scholarly articles, then analyzed using thematic analysis and the Miles and Huberman interactive model. The findings reveal significant differences in epistemology, methodology, and interpretive outcomes. Thanthawi Jauhari adopts an integrative approach by linking dukhan to scientific phenomena, while Mahmud Syaltut applies a textual approach by interpreting it as divine punishment within a historical context. These differences indicate that scientific exegesis represents not only a method but also an epistemological stance that shapes meaning construction. The study highlights the need to position scientific exegesis proportionally to ensure relevance without compromising methodological rigor. The implications include strengthening contemporary tafsir epistemology and providing practical contributions to developing more critical and contextual Islamic education. Future research is recommended to expand the scope and incorporate empirical approaches to examine how scientific exegesis is practiced in society..